A Qualitative Study on Branding of Steel Products in India - Dasari, Shailendra (Indian Journal of Marketing, 2009)
Branding which has traditionally been the forte of B2C products has of late assumed lot of relevance and importance even for B2B products, in the changing global business environment. Steel, one of the core sectors of our economy, has been a highly commoditized product prior to liberalization of Indian economy. With the opening up of the economy and entry of a number of private players, customization and differentiation through strategic brand management has become the "mantra" for growth and survival.